Pengaruh Mindfulness terhadap Subjective Well-Being pada Mahasiswa di Kota Padang - Putri, Sri Adinda Maharani (TSAQOFAH, 2025)
This study aims to examine the effect of mindfulness on subjective well-being among university students residing in Padang City. A quantitative approach with a correlational research design was used. A total of 384 active students from the 2021 to 2023 cohorts were selected through purposive sampling based on specific criteria. Data were collected using two scales: the subjective well-being scale developed by Amanah (2020) and the mindfulness scale developed by Meindy et al. (2022). Data analysis revealed a significance value of 0.035 (p < 0.05) and a correlation coefficient (R) of 0.108. These results indicate a statistically significant effect of mindfulness on subjective well-being, although the strength of the relationship is considered weak. The conclusion of this study is that an increase in mindfulness levels can contribute to enhanced subjective well-being among students, although additional efforts are needed to strengthen this relationship. The implications of this study highlight the importance of mindfulness-based psychological interventions to support students' subjective well-being in higher education environments.